Modernity as the transformation of truth into meaning - Tassi, Aldo (1982)
What characterizes the 'modern' view of things is the fundamental belief that things are to be dealt with only in terms of their reference to human projects. This stands in marked contrast to the belief which constitutes the pre-modern view: namely, That things possess a nature of their own which establishes the terms in which man is to deal with them. The transition from the latter to the former is marked by a shift from a concern for truth to a concern for meaning. The ideal of doing justice to things on "their own" terms is replaced by the ideal of achieving coherence with regard to the terms to which we (in our projects) subject things. The article discusses how Hume and Kant play a decisive role in this transition.
Reprinted and reproduced through the initiative of Alpha Phi Omega Internationals (Phils.) Collegiate Service Fraternity and Sorority, Inc., Gamma Pi Chapter.
Keywords: Modernity and society; Meaning(Philosophy).